Low limit of detection silicon photonic sensor with extremely-low-cost laser source - Leuermann, Jonas; Fernández-Gavela, Adrián; Lechuga, Laura M.; Sánchez-Postigo, Alejandro; Halir, Robert; Molina-Fernández, Íñigo (My University, 2020)
Integrated photonic biosensors have demonstrated low bulk detection limits down to 1e−7 refractive index units. Nevertheless, most rely on expensive optical sources, such as DFB lasers. Here, we experimentally demonstrate that with adequate sensor design comparable detection limits are achievable with a low-cost Fabry-Perot laser.
Keywords: Fotónica; Biosensores; Rayos láser; Biosensing; Silicon photonics; Coherent detection